Investigating Role of Vegetation in Protection of Houses during Floods - Amina Ali; Ghufran Ahmad Pasha; Usman Ghani; Afzal Ahmed; Fakhar Muhammad Abbas (Salehan Institute of Higher Education, 2019)
Flood flows have the potential to cause substantial damage to infrastructure, mankind, livestock and agricultural land which all stacks up to greatly affect the financial condition of the region. During 2010 Pakistan floods, more than two million houses were damaged partly or totally [1]. To minimize these types of destructions, inland vegetation can be considered a natural barrier to dissipate the energy of flood flow and limits widespread inundation. This study involves volume of fluid (VOF) modelling approach to figure out the role of vegetation of finite width in energy reduction of flood flow, in front of houses, against: vegetation of varying Aspect Ratio (A/R width-length ratio) and distance between vegetation & houses (Lr). Channel domain was built in ANSYS workbench toolkit and meshing was done in meshing building toolkit. For the postprocessing and simulation, FLUENT was used. Various contour plots & profiles of cross stream-wise velocities and water level measurements are presented in this paper. The simulation results of cross stream-wise velocities and water level measurements were identical with experimental data. At vegetation upstream and downstream, velocity reduction observed in higher A/R (2.40) compared to vegetation of A/R-1. Whereas, outside the vegetation and near the walls of channel domain flow velocities were high. The water level was raised on the upstream side of the vegetation due to resistance offered by vegetation. On the upstream side of vegetation, the rise in backwater depth increased by increasing A/R. Contrarily, on the downstream side of vegetation, an undular hydraulic jump was observed in between vegetation and a house. By increasing A/R, the energy loss increases under constant vegetation conditions (G/d = 0.24, Fro = 0.70; G = spacing of each cylinder in cross-stream direction and d= diameter of cylinder and Fro = initial Froude number) and increase in house distance from 1W to 2W, the energy reduction increased from 2.40% to 3.15% which was further increased to 5.04% for another 5W increase in house distance, where W is the vegetation width. Simulation results also shown that with increasing Froude no from 0.60 to 0.70 water level depth has also an incremental pattern which ultimately results in increase in energy dissipation along the varying building distance (1W, 2W & 5W). Thus, to minimize the structural damage, a structure must be located at a safe distance away from the vegetation where flow becomes sub-critical.